2018
DOI: 10.1111/jgs.15613
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sarcopenic Obesity and Falls in a Multiethnic Cohort of Postmenopausal Women

Abstract: OBJECTIVES: To prospectively investigate associations of sarcopenia, obesity, and sarcopenic obesity with the incidence of falls in a racially and ethnically diverse cohort of healthy postmenopausal women from the Women’s Health Initiative (WHI). DESIGN: Prospective cohort study. SETTING: Three WHI clinical centers (Tucson-Phoenix, AZ; Pittsburgh, PA; Birmingham, AL). PARTICIPANTS: Postmenopausal women aged 50–79 years enrolled in the WHI who received bone and body composition scans by Dual-Energy X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 43 publications
(93 reference statements)
1
54
0
2
Order By: Relevance
“…Sarcopenia is gradual decrease in muscle strength and function. Declined muscle mass is replaced by fat tissue with consequent increase in obesity (Follis, Cook, Bea, Going, & Laddu, 2018). Sarcopenic individuals have 60% increases in the odds of falling in meta-analysis of studies on elderly ≥ 65 (Yeung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is gradual decrease in muscle strength and function. Declined muscle mass is replaced by fat tissue with consequent increase in obesity (Follis, Cook, Bea, Going, & Laddu, 2018). Sarcopenic individuals have 60% increases in the odds of falling in meta-analysis of studies on elderly ≥ 65 (Yeung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…
We read the article by Follis and colleagues examining the relationship between sarcopenic obesity and falls in a multiethnic cohort of postmenopausal women. 1 We found this article interesting; however, we want to address some points.Although the anabolic effects of androgens are well known, the results of studies examining the effect of estrogen on skeletal muscle are conflicting. Previous studies have shown that hormone replacement therapy (HRT) increased muscle mass and strength in postmenopausal women.
…”
mentioning
confidence: 99%
“…Accordingly, we controlled for HRT as a confounder in the association between sarcopenic obesity and falls. 2 To further address this point, we conducted a sensitivity analysis excluding HRT users. The results for risk of falls yielded similar findings to the total sample (data not shown), in agreement with prior research in the Women's Health Initiative (WHI) cohort.…”
Section: Reply To Effects Of Hormone Replacement Therapy On Sarcopenimentioning
confidence: 99%
“…As the authors indicate, there is some evidence that hormone replacement therapy (HRT) may play an important role in sarcopenia. Accordingly, we controlled for HRT as a confounder in the association between sarcopenic obesity and falls . To further address this point, we conducted a sensitivity analysis excluding HRT users.…”
mentioning
confidence: 99%